Reaction of 2-alkylidene-3, 1-benzoxathiin-4-ones with nitrones. (1st February 2017) - Shimizu, Masao; Yamanaka, Masaki; Kurita, Koujiro; Tanaka, Shinji; Ando, Wataru; Sakai, Norio
GRAPHICAL ABSTRACT: ABSTRACT: 2-Methylene-3, 1-benzoxathiin-4-ones reacted with nitrones at methylene moieties of 3, 1-benzoxathiine rings to yield spiro 1, 3-dipolar cycloadducts. The benzoxathiin-4-one rings easily occurred ring opening reaction with NaOSiMe3 and isoxazolidin-5-one derivatives were obtained in good yields. As a result, 2-methylene-3, 1-benzoxathiin-4-ones can be used as a ketene equivalent.